IMPLEMENTASI METODE TWO STAY TWO STRAY TERHADAP PENGUASAAN MUFRADĀT SISWA - Muwafiquddin, Achmad; Anwar, Najih (STIQ Amuntai, 2024)
Vocabulary is one of the fundamental elements in active and passive language use. To reach a mastery phase, one must be capable of applying vocabulary in communication, writing, reading, and understanding words as well as sentences. To support the mastery of vocabulary, an engaging learning method known as the